Diseño y construcción de un prototipo de refrigerador solar con ciclo de adsorción carbón activo metanol. - Jaramillo Tamayo, Byron Vinicio (2013)
This study is part of the design, construction and testing of a prototype solar cycle refrigerator activated carbon adsorption - methanol. The pair activated carbon adsorption and methanol ECOK-70 presents different constants of the equilibrium equation Dubinin Astakhov (DA), which were determined by a procurement team isósteras, calculating the following constants: n = 1.18, W0 = 0.138L/kg and DD-A = 3.48E-4, used in the design of solar refrigerator. For the design of the system is considered material and technology available in our town, dividing it into several subsystems, starting from the basic functional refrigerator itself, until the system coupling solar energy collection. The cooling system consists basically of: a solar collector, the heat chamber, condenser and cold chamber.